The impact of decentralized decision making on student outcomes and teacher quality: Evidence from Colombia - Gregory Elacqua; Isabela Munevar; Fabio Sánchez Torres; Humberto Santos (Inter-American Development Bank (IDB), 2019)
To contribute to the debate about decentralization of education management, in this paper, we take advantage of the arbitrary rule used in Colombia to define the municipalities that can autonomously manage schools, to evaluate through a Regression Discontinuity methodology the effect of municipal's autonomy on student achievement and teacher characteristics, using as a counterfactual schools located in municipalities that just missed the population criteria, schools that are managed by the departments. Our results suggest that schools in municipalities that became autonomous in terms of their public education administration, have on average, a lower proportion of low-performing students, than similar schools in municipalities that do not manage their schools, especially in 9th grade. Moreover, when analyzing the teachers' characteristics as a channel to explain academic performance, we found that teachers in certified municipalities score on average, 0.5 to 1 standard deviation higher on the mandatory competency test to become a permanent public-school teacher.
Keywords: I22; I28; H75; 330; Education decentralization; Colombia; educational achievement; teacher quality